Fertilizer quality assessment: Perception versus testing in selected Ghanaian districts - Asante, Seth; Simons, Andrew M.; Andam, Kwaw S.; Amprofi, Felicia Ansah; Osei-Assibey, Ernest; Iddrisu, Adisatu (International Food Policy Research Institute, 2021)
Fertilizer use in Sub-Saharan Africa remains below recommended rates, contributing to low yields, and increasing poverty. Poor quality fertilizer – whether perceived or real – is often cited as a reason for low adoption rates. In Ghana, for example, there are widespread but often unsubstantiated claims of substandard fertilizers. This is a concern for farmers with limited purchasing power and without the means to independently substantiate the quality of agricultural inputs. This paper describes the agricultural input sector in Ghana, compares farmers’ perception of fertilizer quality with those of input dealers, and analyses chemical tests of fertilizers performed in a laboratory. The fertilizers were sampled from selected districts participating in the Planting for Food and Jobs initiative, a large-scale farm input subsidy program. We find that input dealers and farmers are somewhat suspicious of the quality of commercially supplied and government subsidized fertilizers. However, the true quality measures based on laboratory testing of fertilizers sold in agricultural input shops were found to largely meet the labeled chemical composition.